2021
DOI: 10.1002/fsn3.2605
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics study of Angelica sinensis (Oliv.) Diels on the abnormal uterine bleeding rats by ultra‐performance liquid chromatography–quadrupole–time‐of‐flight mass spectrometry analysis

Abstract: The objective of this study was to explore the effects and underlying intervention mechanisms of Angelica water extract (AWE) on abnormal uterine bleeding (AUB) based on serum metabolomics. Firstly, the concentration of main active substances in AWE was determined and the chemical components were identified by UPLC‐Q‐Exactive Orbitrap‐MS/MS. A drug‐induced abortion model was established by mifepristone and misoprostol. After administration AWE (2.16 g/kg) for 7 days, the coagulation function, serum hormone lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…As the final product of lipid peroxidation, the content of MDA could reflect the damage degree of lipid peroxidation ( Jiang W. et al, 2021 ). T-SOD, GSH, and GPx are liver oxidation active enzymes, which could remove peroxides and free radicals, alleviate liver damage and protect hepatocytes ( Li et al, 2018 ; Xie et al, 2020b ; Li Z. et al, 2021 ; Yang et al, 2021 ), and were considered as important indicators reflecting hepatic oxidative damage ( Park et al, 2019 ; Chen T. et al, 2021 ). Consequently, after confirming that processing with ASR could significantly improve the liver toxicity induced by RDB, the potential molecular mechanism of ASR-processed RDB to reduce its liver toxicity was evaluated by detecting and analyzing Nrf2 and its downstream-related molecules.…”
Section: Discussionmentioning
confidence: 99%
“…As the final product of lipid peroxidation, the content of MDA could reflect the damage degree of lipid peroxidation ( Jiang W. et al, 2021 ). T-SOD, GSH, and GPx are liver oxidation active enzymes, which could remove peroxides and free radicals, alleviate liver damage and protect hepatocytes ( Li et al, 2018 ; Xie et al, 2020b ; Li Z. et al, 2021 ; Yang et al, 2021 ), and were considered as important indicators reflecting hepatic oxidative damage ( Park et al, 2019 ; Chen T. et al, 2021 ). Consequently, after confirming that processing with ASR could significantly improve the liver toxicity induced by RDB, the potential molecular mechanism of ASR-processed RDB to reduce its liver toxicity was evaluated by detecting and analyzing Nrf2 and its downstream-related molecules.…”
Section: Discussionmentioning
confidence: 99%
“…As an effective preparation for the treatment of PD, the main components of DSS, such as chlorogenic acid, levistilide A, senkyunolide A, have shown good therapeutic effects in PD, uterine bleeding, and inflammatory activities ( Saltan et al, 2016 ; Chen et al, 2021 ; Zhang et al, 2021 ). Through the analysis of body weight, uterine organ index, and writhing behavior, it was found that the body weight of rats recovered to a certain extent, and the uterine index, writhing latency, and writhing times could be significantly improved after the continuous administration of DSS for 10 days.…”
Section: Discussionmentioning
confidence: 99%
“…was analyzed by comparing with the information described in the reference, and the detailed process was as follows: the chemical constituent was identified via precursor ion, fragment ions, and MS fragmentation pathways on Xcalibur 4.1.31 software (Thermo Scientific, USA). CX (Qin et al 2022;Shen et al 2022), DG (Chen et al 2021;Wang et al 2021), YZ (Gao et al 2021), SZ (Shao et CX (Zhang, Yang, et al 2015), DG (Zhang et CX (Qin et al 2022), DG (Chen et al 2021;Wang et al 2021), SQ (Wang et al 2021), SCP (Li, Chen, et al 2019), SZ (Ao et al 2020), CNX (Cao 2017), DS (Zou et al 2021;Liang et al 2017)…”
mentioning
confidence: 99%